EKSPLORASI PENGALAMAN GURU DALAM MENGINTEGRASIKAN PENDEKATAN DEEP LEARNING DI MI TARBIYATUL ISLAMIYAH GEMBONG PATI - Arif Billah, Moh Shohibul Wafa; Rufa Hindun Farhisiyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study explores teachers’ experiences in integrating the deep learning approach at MI Tarbiyatul Islamiyah Gembong Pati. The transformation of educational paradigms in the 21st century requires a shift from surface learning to meaningful and reflective learning practices. However, the implementation of deep learning in Islamic elementary schools remains contextually dynamic and dependent on teachers’ professional experiences. This research aims to describe teachers’ understanding of deep learning, the strategies employed in classroom practices, the perceived impact on students’ learning processes, and the challenges encountered during implementation. The study employed a qualitative approach with a phenomenological design to capture teachers’ lived experiences. Data were collected through in-depth interviews, classroom observations, and document analysis. The findings reveal that teachers perceive deep learning as a student-centered approach that emphasizes conceptual understanding, contextual relevance, and reflective thinking. Teachers applied strategies such as contextual discussions, reflective questioning, and problem-based activities to enhance students’ engagement and critical thinking skills. The implementation resulted in increased student participation and deeper conceptual comprehension. However, challenges such as limited instructional time, diverse student abilities, and infrastructural constraints were identified. The study concludes that integrating deep learning in Islamic elementary education requires pedagogical readiness, institutional support, and sustained professional development to ensure meaningful and transformative learning experiences.